2003
DOI: 10.1002/hbm.10122
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus repetition and hemodynamic response refractoriness in event‐related fMRI

Abstract: Abstract:We investigated the extent of hemodynamic recovery following the paired presentation of either identical or different faces at two different inter-stimulus intervals (ISI). Signal recovery was consistently better at an ISI of 6 sec compared to 3 sec. Significantly less signal recovery was associated with identical faces compared to different faces in bilateral mid-fusiform and right prefrontal regions but not in the calcarine and posterior fusiform regions. Repetition suppression effects contributed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 56 publications
3
31
0
Order By: Relevance
“…Schlaggar et al (2002) reported age-related activation differences independent of language tasks, which may reflect general cognitive factors. Indeed, previous neuroimaging studies have reported a repetition priming effect in which the repeated presentation of visual objects resulted in an activation decrease in broad regions, including the frontal and occipital cortices (Schacter and Buckner, 1998;Van Turennout et al, 2000;Dehaene et al, 2001;Soon et al, 2003). Because the order of tasks was counterbalanced across subjects in the present study, the repetition or familiarization effects on activation, if any, cannot explain the results of JP-JM (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Schlaggar et al (2002) reported age-related activation differences independent of language tasks, which may reflect general cognitive factors. Indeed, previous neuroimaging studies have reported a repetition priming effect in which the repeated presentation of visual objects resulted in an activation decrease in broad regions, including the frontal and occipital cortices (Schacter and Buckner, 1998;Van Turennout et al, 2000;Dehaene et al, 2001;Soon et al, 2003). Because the order of tasks was counterbalanced across subjects in the present study, the repetition or familiarization effects on activation, if any, cannot explain the results of JP-JM (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…These findings could be explained by stimulus repetition effects. Such effects have been observed in the PPA [Epstein et al, 1999Menon et al, 2000] and the FFA [Eger et al, 2004;Ishai et al, 2004;Soon et al, 2003;Vuilleumier et al, 2003], although the opposite finding has also been observed [Henson, 2003]. Interestingly, these repetition effects were specific to scenes in the PPA, but were not specific to faces in the FFA.…”
Section: Ffa and Ppa Activitymentioning
confidence: 72%
“…A large number of prior studies have documented failures of temporal superposition in fMRI data (Boynton et al, 1996;Dale and Buckner, 1997;Robson et al, 1998;Vazquez and Noll, 1998;Glover, 1999;Ances et al, 2000b;Huettel and McCarthy, 2000;Liu and Gao, 2000;Birn et al, 2001;Huettel and McCarthy, 2001;Miller et al, 2001;Boynton and Finney, 2003;Soon et al, 2003;Huettel et al, 2004a,b;Soltysik et al, 2004;Gu et al, 2005;Murray et al, 2006). Other studies have found additional nonlinearities in fMRI; for example, when neural activity increases by a certain percentage, fMRI response fails to increase by the same percentage (e.g., Logothetis et al, 2001;Devor et al, 2003;Jones et al, 2004;Sheth et al, 2004;Hewson-Stoate et al, 2005;Wan et al, 2006).…”
Section: Complex Models Of Nonlinearities In Rapid Er Fmrimentioning
confidence: 99%
“…If superposition holds, then subtracting the response to an individual event from the response to a sequence of two events should yield a response that is identical in shape to the individual response. In actual fMRI data the subtracted response is smaller, often as little as 60-70% of the individual response (Dale and Buckner, 1997;Glover, 1999; McCarthy, 2000, 2001;Boynton and Finney, 2003;Soon et al, 2003;Huettel et al, 2004a;Murray et al, 2006). Similar nonlinearities in response occur in sequences of blocks of events (Boynton et al, 1996;Robson et al, 1998;Vazquez and Noll, 1998;Glover, 1999;Ances et al, 2000b;Liu and Gao, 2000;Birn et al, 2001;Miller et al, 2001;Huettel et al, 2004b;Soltysik et al, 2004;Gu et al, 2005).…”
mentioning
confidence: 99%